"Since when the dimension of things is expressed in grams?" The pragmaticalization of 'desde cuándo' (≈ since when) - Patricia Carmen Hernández (Philologia Hispalensis, 2016)
This paper deals with the non-temporal values of the interrogative form desde cuándo (≈ ‘since when’) in expressive utterances. According to the theoretical framework of Cognitive Linguistics, these cases can be characterized as pragmaticalized i.e. showing the speaker’s subjectivity. In this way, desde cuándo becomes a discourse marker suggesting some kind of discordance. We describe the uses of this linguistic form by analyzing a corpus of utterances. Such study allows us to propose a first typology of the uses of this marker.